Medicine & Health Care in Early Christianity - Borgongino, Bruno Uchoa (Revista Crítica Histórica, 2017)
FERNGREN, Gary B. Medicine & Health Care in Early Christianity. Baltimore: The Johns Hopkins University, 2009.